READINESS OF GEOGRAPHY EDUCATION STUDENTS TO FACE THE DEMOGRAPHIC BONUS BASED ON SOFT SKILLS AND HARD SKILLS - Frandica Panjaitan; Dede Sugandi; Nina Novira (Universitas Sebelas Maret (UNS), 2025)
This study aims to (1) find out the level of knowledge of students of the Department of Geography Education class of 2020-2023 regarding the demographic bonus, (2) find out the Readiness of soft skills of students of the Department of Geography Education class of 2020-2023. (3) knowing the Readiness of hard skills of students of the Department of Geography Education class of 2020-2023. This research was conducted at the Department of Geography Education, State University of Medan, in April 2024. The population of this study is 542 students, and the Researcher took 10% of the total population, namely 55 students. The data collection technique in this study is in-depth interviews. The data analysis technique used is qualitative descriptive analysis. The study results show that: (1) As many as 45% of geography education students of the 2020-2023 batch know the demographic bonus. (2) The Readiness of students of the Department of Geography Education class of 2020-2023 based on soft skills is in the category of unprepared. (3) The Readiness of students of the Department of Geography Education class of 2020-2023 based on soft skills is in the category of unpreparedness. So it can be concluded that students majoring in geography education class 2020-2023 are not ready to face the demographic bonus and must improve their soft and hard skills. Based on these things, the government and also campuses must strengthen the teaching of soft skills and hard skills either through training, workshops or internships that focus on developing these skills.